IL-33 Regulates the Phenotypic Transformation of Reactive Astrocytes via PENK-ERK/MAPK Pathway in Parkinson’s Disease - Yi Qu; Zhijuan Mao; Danlei Wang; Ke An; Haoheng Yu; Qixiong Qin; Jingyi Li; Yongjie Xiong; Zhe Min; Zheng Xue (Neuroscience Bulletin, 2026)
Interleukin-33 (IL-33) regulates immune responses in central nervous system diseases. This study investigates the effect of IL-33 on astrocyte phenotypic transformation in Parkinson’s disease (PD). The associations of IL-33, soluble growth-stimulating expression gene 2 (sST2), with PD severity and clinical symptoms were examined. IL-33 supplementation and knockdown were applied in vivo and in vitro to assess IL-33’s impact on neuron loss, astrocyte polarization, and inflammation. Transcriptome sequencing was conducted to identify hub genes and pathways regulated by IL-33 in astrocytes, with validated in primary astrocytes. Plasma sST2 levels were elevated in PD patients and correlated with PD severity, while IL-33 decreased with disease progression. In PD models, IL-33 supplementation improved PD-like symptoms and A2 astrocyte polarization. Conversely, IL-33 knockdown worsened PD-like symptoms and neurotoxic polarization. RNA-seq identified the PENK-ERK/MAPK pathway as the key regulator of IL-33-mediated astrocyte transformation. In conclusion, IL-33 plays a crucial role in regulating astrocytes in PD.